Transgenic expression of antimicrobial peptides from insects as a tool for analysis of compatibility between plants and pathogens - Khalifa, Walaa Said Mohamed Shaaban; Justus Liebig University Giessen (My University, 2010)
Genetic engineering has proven to be a powerful tool for controlling plant diseases and tobe an alternative to economically costly and environmentally undesirable chemical control.One promising approach to achieve enhanced disease-resistance has been through theexpression of genes encoding antimicrobial peptides (AMPs) in transgenic plants. Hence,this study aimed to investigate the feasibility of using the novel insect AMP EtDef, adefensin from drone fly Eristalis tenax and the well-known AMP thanatin from spinedsoldier bug Podisus maculiventris to engineer disease resistance in the model plantArabidopsis.A prerequisite for the utilization of these peptides is a precise knowledge about theirbiological activity. Thus, in vitro antifungal activity of the chemically synthesized EtDefand thanatin was evaluated against the devastating phytopathogens F. culmorum, B.cinerea and P. parasitica using spore germination inhibition assays. Results of these assaysrevealed that synthetic EtDef led to total inhibition of spore germination and mycelialgrowth of all tested fungi, with minimum inhibitory concentrations (MICs) varyingbetween 1 - 2 for B. cinerea and 5 - 10 µM for F. culmorum and P. parasitica. Syntheticthanatin showed higher efficacy as compared to EtDef regarding inhibitory effects. Therethe MICs ranged between 0.5 - 1 µM for B. cinerea, 5 - 10 µM for F. culmorum, and 2 - 5µM for P. parasitica.Concomitantly, a protocol for the production of recombinant EtDef in E. coli expressionsystem was established by inserting the sequence for mature EtDef peptide in framedownstream of the multiple tag TrxA - His -S of pET32a(+) vector. The resultingrecombinant THS-EtDef protein was then refolded and its in vitro biological activity wasevaluated against B. cinerea using spore germination inhibition assay. It was observed thatTHS-EtDef showed also a similar antifungal activity to the chemically synthesizedcounterpart, with IC50 occurred at 0.5 µM. This indicates that the presence of the tag,which is bigger than the AMP peptide, didn´t much alter the activity of EtDef in vitro.Because of their promising antimicrobial properties, EtDef (with its putative signalpeptide) and the chimeric thanatin (containing HvChi26 signal peptide) were introducedinto Arabidopsis via Agrobacterium-mediated transformation and expressed under thecontrol of the constitutive CaMV35S promoter. Molecular characterization analysisrevealed that both EtDef and thanatin genes were efficiently transcribed into mRNA,although the levels of expression varied among transformants.Due to the signal peptides both AMPs are thought to enter the secretory pathway. Thereforintercellular washing fluids (IWFs) from individual transgenic plants expressing eitherEtDef or thanatin were isolated. Spore germination of B. cinerea was inhibited to variousdegrees, indicating that the expression of these peptides was functional and localized toextracellular space in all transgenic lines tested.The degree of resistance achieved by expressing either EtDef or thanatin were thenevaluated in planta against the fungal pathogens G. orontii and B. cinerea and the bacterialpathogen P. syringae pv. tomato strain DC3000. EtDef and thanatin transgenic Arabidopsisplants displayed remarkably reduced conidial sporulation, hyphal spread and proliferationof G. orontii on the rosette leaves, mediating enhanced disease resistance in these plants.This suppressive effect against G. orontii was correlated with RNA expression level. Threeindependent EtDef transgenic lines namely 395, 396, and 405 and thanatin transgenic lines407, 410, and 411 showed high RNA expression levels, and correspondingly highresistance degree to G. orontii. In contrast, transgenic expression of EtDef and thanatin inArabidopsis was clearly less active against B. cinerea. Nevertheless, two EtDef transgeniclines 396 and 405 and two thanatin transgenic lines 410 and 411 were consistently moreresistant against B. cinerea. When challenged with Pst, all transgenic EtDef lines were assensitive as the control plants, except for transgenic line 405. Transgenic expression ofthanatin in Arabidopsis could provide, however, a higher degree of resistance against Pst.Thanatin transgenic lines 407, 410, and 411, showed the highest resistance to Pst. Insummary, plants of the EtDef transgenic lines 395, 396, 398 and 405 and those of Thanatin407, 410 and 411 seem to be promising candidates to evaluate their potential in plantaagainst other phytopathogens. Finally, data presented here indicate that transgenicexpression of EtDef and Thanatin could be utilized to improve disease resistance of othereconomically important crops.

Gentechnische Methoden haben sich als wichtiges Werkzeug zur Kontrolle vonPflanzenkrankheiten erwiesen und bilden eine Alternative zum kostenintensiven undökologisch unerwünschten Einsatz von Chemikalien. Als viel versprechender Ansatz zurSteigerung der Resistenz gegen Krankheiten hat sich die Expression von Genen intransgenen Pflanzen erwiesen, die für antimikrobielle Peptide (AMPs) kodieren. Ziel derhier vorgestellten Studie war es daher zu untersuchen, inwieweit sich EtDef, ein neuesPeptid aus der Schwebfliege Eristalis tenax, und das gut untersuchte AMP Thanatin ausder Raubwanze Podisus maculiventris zur Erhöhung der Krankheitsresistenz derModellpflanze Arabidopsis thaliana nutzen lassen.Voraussetzung für den Einsatz dieser Peptide ist ein präzises Wissen um deren biologischeWirkung. Aus diesem Grund wurde zu Beginn in Sporenkeimungstests die antimykotischeWirkung von synthetisch hergestelltem EtDef und Thanatin auf die phytopathogenen PilzeF. culmorum, B. cinerea und P. parasitica untersucht. Synthetisches EtDef führte hierbeizu einer vollständigen Inhibierung der Sporenkeimung und des Myzelwachstums bei allengetesteten Pilzen mit miminimalen Hemm-Konzentrationen (MHK) von 1 - 2 µM für B.cinerea und 5 - 10 µM für F. culmorum und P. parasitica. Für synthetisches Thanatinwurde eine größere inhibitorische Wirksamkeit als für EtDef beobachtet. Die minimalenKonzentrationen zur vollständigen Hemmung lagen hier bei 0,5 - 1 µM für B. cinerea, 5 -10 µM für F. culmorum und 2 - 5 µM für P. parasitica.Parallel zu diesen Experimenten wurde ein Protokoll zur Produktion von rekombinantemEtDef in E. coli etabliert. Hierzu wurde die Sequenz des EtDef Peptids in frame abwärtsdes TrxA - His - S Tags des pET32a(+) Vektors inseriert. Die biologische Aktivität deshergestellten THS-EtDef Proteins wurde in vitro überprüft, wofür wiederum dieInhibierung der Sporenkeimung bei B. cinerea untersucht wurde. Es konnte eine ähnlicheantimykotische Wirkung für THS-EtDef wie bei synthetischem EtDef gezeigt werden. Dasdeutet darauf hin, dass die Aktivität von THS-EtDef in vitro nur gering durch den Tag, dergrößer als das AMP selbst ist, beeinflusst wird.Aufgrund der viel versprechenden antimikrobiellen Eigenschaften wurden mittelsAgrobacterium-vermittelter Transformation Arabidopsis-Pflanzen erstellt, die EtDef (mitseinem putativen Signalpeptid) oder chimäres Thanatin (mit dem pflanzlichen SignalpeptidHvChi26) unter Kontrolle des konstitutiven CaMV35S Promotors exprimieren.Molekularbiologische Tests zeigten, dass sowohl das EtDef-, als auch das Thanatingeneffizient in mRNA transkribiert wurden, wobei zwischen einzelnen Transformantenvariierende Expressionslevel nachgewiesen wurden.Die vorgeschalteten Signalpeptide sollten zur Sekretion der AMPs in den Apoplastenführen. Deshalb wurden von individuellen transgenen Pflanzen, die entweder EtDef oderThanatin exprimierten intercellular washing fluids (IWFs) isoliert. Die Sporenkeimung vonB. cinerea wurde im Vergleich zur Kontrolle bei den verschiedenen Linien inunterschiedlichem Ausmaß inhibiert. Das deutet darauf hin, dass die Peptide in allenuntersuchten Linien funktionell und im extrazellulären Raum lokalisiert waren.Im Folgenden wurde der Grad der Resistenz, der durch die Expression von entweder EtDefoder Thanatin hervorgerufen wurde, in planta untersucht. Hierfür wurden die pilzlichenPathogene G. orontii und B. cinerea und das bakterielle Pathogen P. syringae pv. tomatoDC3000 (Pst) verwendet. Transgene Arabidopsis Pflanzen mit entweder EtDef oderThanatin zeigten eine deutlich verringerte Sporulation der Konidien, verringertesMyzelwachstum und Vermehrung von G. orontii auf Rosettenblättern, was zu einererhöhten Resistenz der Pflanzen gegen diesen Pilz führte. Der Effekt auf G. orontiikorrelierte mit der Transcriptmenge in den Pflanzen. Drei unabhängige transgene EtDef-(395, 396 und 405) und drei Thanatin-Linien (407, 410 und 411) wiesen hohe RNAExpressionslevelauf, was mit einem hohen Grad an Resistenz gegen G. orontii einherging.Im Gegensatz dazu zeigte die Expression von EtDef und Thanatin in Arabidopsis einedeutlich geringere Wirkung auf B. cinerea. Gleichwohl zeigten zwei transgene EtDef- (396und405) und zwei transgene Thanatin-Linien (410 und 411) eine gesteigerte Resistenzgegen diesen Pilz. In den EtDef-Linien konnte eine erhöhte Resistenz gegenüber Pst nur inLinie 405 beobachtet werden. Die Sensitivität der übrigen Linien gegenüber demBakterium war nicht signifikant unterschiedlich zu den Kontrollpflanzen. Jedochvermittelte die transgene Expression von Thanatin eine deutlich erhöhte Resistenz derPflanzen gegen Pst. Hier zeigten wiederum die transgenen Linien 407, 410 und 411 diestärkste Wirkung. Zusammengefasst erscheinen die Linien 395, 396, 398 und 405 und 407,410 und 411 am besten geeignet, um in weiteren Untersuchungen das Potential von EtDefbzw. Thanatin gegen andere Phytopathogene in planta zu testen. Die in dieser Studiepräsentierten Ergebnisse deuten darauf hin, dass die transgene Expression von EtDef undThanatin genutzt werden könnte, um eine gesteigerte Resistenz gegenüber Krankheitenauch in anderen, ökonomisch wichtigen, Pflanzen zu erzielen.
xx
Keywords: antimicrobial peptides; transgenic plants; insects; plant pathogens; ddc:570